2011
DOI: 10.1016/s1995-7645(11)60164-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial potential of some Vitex species against human pathogenic bacteria

Abstract: Based on the present study, V. peduncularis is recommended for the isolation of antibacterial molecule responsible for the activity against the tested human pathogenic bacterial strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…There are several reports published on antibacterial activity of different herbal extracts [18][19][20][21][22][23][24][25] . It supports the earlier investigation that the tannins isolated from the flower possess remarkable toxic activity against bacteria and may assume pharmacological importance [26][27][28][29][30][31][32][33][34][35][36][37][38] . Many antimicrobial screening studies use a relatively small number of microorganisms for testing.…”
Section: Discussionsupporting
confidence: 87%
“…There are several reports published on antibacterial activity of different herbal extracts [18][19][20][21][22][23][24][25] . It supports the earlier investigation that the tannins isolated from the flower possess remarkable toxic activity against bacteria and may assume pharmacological importance [26][27][28][29][30][31][32][33][34][35][36][37][38] . Many antimicrobial screening studies use a relatively small number of microorganisms for testing.…”
Section: Discussionsupporting
confidence: 87%
“…The differences in the antimicrobial activity of crude extracts may be due to the amount of antimicrobial agent present in the extract (Barbour et al, 2004). The present study showed the highest antimicrobial activity with lower MIC values and the same trend was observed by Kannathasan et al, 2011. The methanol extract of V. peduncularis showed the highest mean zone of inhibition (22.670 ±0.667 mm) and the lowest MIC (62.5 μg /mL) and MBC values (125.0 μg /mL) against S. aureus followed by M. luteus (21.670 ±0.667 mm; MIC (62.5 μg /mL).…”
Section: Discussionsupporting
confidence: 77%
“…These findings do not correlate with the observations of previous screenings of medicinal plants for antimicrobial activity, where most of the active plant extracts showed activity against Gram-positive strains only [56][57][58][59] . Because Gram-negative organisms were reported to be less susceptible to the action of antibacterials, since they possess an outer membrane surrounding the cell wall, which restricts diffusion of hydrophobic compounds through its lipopolysaccharide covering [60][61][62][63][64][65][66][67] . Besides the difference in sensitivity might be ascribed to the difference in morphological constitutions between Gram-positive and Gram-negative organisms.…”
Section: Discussionmentioning
confidence: 99%